Pathways to Prohibition : Radicals, Moderates, and Social Movement Outcomes - Szymanski, Ann-Marie E., 1967- (Book collections on Project MUSE., 2003)
Strategies for gradually effecting social change are often dismissed as too accommodating of the status quo. Ann-Marie E. Szymanski challenges this assumption, arguing that moderation is sometimes the most effective way to achieve change. Pathways to Prohibition examines the strategic choices of social movements by focusing on the fates of two temperance campaigns. The prohibitionists of the 1880s gained limited success, while their Progressive Era counterparts achieved a remarkable -- albeit temporary -- accomplishment in American politics: amending the United States Constitution. Szymanski accounts for these divergent outcomes by asserting that choice of strategy (how a social movement defines and pursues its goals) is a significant element in the success or failure of social movements, underappreciated until now. Her emphasis on strategy represents a sharp departure from approaches that prioritize political opportunity as the most consequential factor in campaigns for social change. Combining historical research with the insights of social movement theory, Pathways to Prohibition shows how a locally based, moderate strategy allowed the early-twentieth-century prohibition crusade both to develop a potent grassroots component and to transcend the limited scope of local politics. Szymanski describes how the prohibition movement's strategic shift toward moderate goals after 1900 reflected the devolution of state legislatures' liquor licensing power to localities, the judiciary's growing acceptance of these local licensing regimes, and a collective belief that local electorates, rather than state legislatures, were best situated to resolve controversial issues like the liquor question. "Local gradualism" is well suited to the porous, federal structure of the American state, Szymanski contends, and it has been effectively used by a number of social movements, including the civil rights movement and the Christian right